TENDENCIES OF DEVELOPMENT OF IMMIGRATION SCHOOLING IN THE XX CENTURY - Віталій Мацько (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2015)
The article deals with objective and subjective tendencies of development of primary, secondary and higher education in the countries west, inhabited by immigrants from Ukraine. It is proved that during the XX century Ukrainian emigration schooling went that evolutional way, which other nations did in foreign environment. Unlike schools that existed in the USSR, the emigrants kept schools at their own expense and only in some cases the state assumed the obligation to teach Ukrainian children (Czechoslovakia, Canada). In the history of pedagogy the activity of school of Ukrainian studies outside the motherland - is a unique example of preservation of national identity, instilling in the younger generation the knowledge about Ukraine, its customs and traditions. The practice proves that children, who learned early the basics of the Ukrainian language and literature in foreign environment, fluently speak their native language during their lives.